2022
DOI: 10.1101/2022.05.02.22274436
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Omicron infection induces low-level, narrow-range SARS-CoV-2 neutralizing activity

Abstract: BackgroundThe rapid worldwide spread of the mildly pathogenic SARS-CoV-2 Omicron variant has led to the suggestion that it will induce levels of collective immunity that will help putting an end to the COVID19 pandemics.MethodsConvalescent serums from non-hospitalized individuals previously infected with Alpha, Delta or Omicron BA.1 SARS-CoV-2 or subjected to a full mRNA vaccine regimen were evaluated for their ability to neutralize a broad panel of SARS-CoV-2 variants.FindingsPrior vaccination or infection wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 23 publications
4
12
0
Order By: Relevance
“…In high-income countries, vaccination programs have contributed to high prevalence of anti-SARS-CoV-2 antibodies particularly among elderly people and individuals with chronic conditions (1)(2)(3), two groups with high risk of severe COVID-19, hospitalization, and death (4,5). While population-based serosurveys remain important to monitor the pandemic (6), they fall short in shedding light on the state of population-level protection against infection from current SARS-CoV-2 variants (7)(8)(9)(10). In fact, studies on neutralizing antibodies, primarily based on small and nonrepresentative samples (11), have shown that neutralizing capacity depends strongly on how antibodies are mounted (through vaccination and/or infection; and the number, duration and severity of infection episodes) and may differ between variants (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In high-income countries, vaccination programs have contributed to high prevalence of anti-SARS-CoV-2 antibodies particularly among elderly people and individuals with chronic conditions (1)(2)(3), two groups with high risk of severe COVID-19, hospitalization, and death (4,5). While population-based serosurveys remain important to monitor the pandemic (6), they fall short in shedding light on the state of population-level protection against infection from current SARS-CoV-2 variants (7)(8)(9)(10). In fact, studies on neutralizing antibodies, primarily based on small and nonrepresentative samples (11), have shown that neutralizing capacity depends strongly on how antibodies are mounted (through vaccination and/or infection; and the number, duration and severity of infection episodes) and may differ between variants (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…This has implications for current immune landscapes shaped by complex age-specific vaccination and infection patterns. Vaccination-induced antibodies have demonstrated high neutralizing capacity against previously predominant variants (ancestral D614G, Alpha, and Delta), but substantially less neutralizing capacity against more recent and currently dominant Omicron subvariants (8,9,12,13)—even though, importantly, protection against severe disease, hospitalization, and death remains high (14,15). Simultaneously, antibodies developed through infection by the Omicron BA.1 subvariant have shown reduced neutralizing capacity against most other variants of concern (VOCs) (8,9,13,16,17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventeen studies analyzed the efficacy of CCP and VaxCCP against Omicron sublineages other than BA.1 (summarized in Table 2 ). Those studieslargely confirmed that Omicron CCP per se is poorly effective against the cognate or other Omicron sublineages 22 (with the lone exception of cross-reactions among lineages sharing L452 mutations 23 and broad-spectrum nAbs elicited by BA.5 24 ). On the contrary, both homologous and heterologous efficacy of Omicron VaxCCP is again universally preserved 15 , 25 .…”
Section: Resultsmentioning
confidence: 73%
“…BA.1 CCP against BA.1: BA.1 breakthrough infection in fully vaccinated es rapidly elicited potent cross-reactive broad nAbs against VOCs Alpha, Beta, Gamma, Delta and BA.1, from unmeasurable IC 50 values to mean 1:2929 at around 9-12 days, which were higher than the mean peak IC 50 values of BNT162b2 vaccinees 26,27 . Convalescent serums only displayed low level of neutralization activity against the cognate virus and were unable to neutralize other SARS-CoV-2 variants 28 .…”
Section: Resultsmentioning
confidence: 99%